Immobilized Fe3O4-Polydopamine-Thermomyces lanuginosus Lipase-Catalyzed Acylation of Flavonoid Glycosides and Their Analogs: An Improved Insight Into Enzymic Substrate Recognition - Wang, Zhaoyu; Li, Yang; Li, Mingyi; Zhang, Xiaohui; Ji, Qingxia; Zhao, Xiaojuan; Bi, Yanhong; Luo, Si (Frontiers in Bioengineering and Biotechnology, 2021)
The conversion of flavonoid glycosides and their analogs to their lipophilic ester derivatives was developed by nanobiocatalysts from immobilizing Thermomyces lanuginosus lipase (TLL) on polydopamine-functionalized magnetic Fe3O4 nanoparticles (Fe3O4-PDA-TLL). The behavior investigation revealed that Fe3O4-PDA-TLL exhibits a preference for long chain length fatty acids (i.e., C10 to C14) with higher reaction rates of 12.6–13.9 mM/h. Regarding the substrate specificity, Fe3O4-PDA-TLL showed good substrate spectrum and favorably functionalized the primary OH groups, suggesting that the steric hindrances impeded the secondary or phenolic hydroxyl groups of substrates into the bonding site of the active region of TLL to afford the product.